The management model to enhance French teaching and learning quality: A case study of a university in Guangxi, China - Jia, Chen; Niramitchainont, Poschanan (Edelweiss Applied Science and Technology, 2025)
With the continuous growth of China–France economic and trade relations (trade volume of USD 78.9 billion in 2023) and China becoming France’s largest trading partner outside the European Union, the demand for skilled French language professionals in China has significantly increased. In response to this growing societal need, it has become imperative to enhance the quality of French language education. This study conducted a needs assessment among students and teachers majoring in French to examine both the current and anticipated conditions related to five key factors: curriculum, teachers, teaching materials, evaluation systems, and learning practices. The primary objective of the research was to identify the specific needs of these stakeholders and to design a management model aimed at improving the quality of French language teaching and learning at a university in Guangxi, China. Findings revealed the prioritized needs of both students and teachers based on the Priority Needs Index (PNI) for the five variables. Notably, the variable "curriculum" recorded the highest PNI scores for both groups, indicating it as the most critical area for development in the proposed model. Based on these results, a management model comprising five components was constructed to enhance the overall quality of French teaching and learning.